Preparation method and application of self-supporting VO2 nanosheet electrode
By introducing oxygen vacancy between VO2 and the carbon cloth, building V-C bonds, and preparing self-supported VO2 nanosheet electrodes, the problem of structural stability and low conductivity of the positive electrode material of zinc ion battery is solved, and the circulation of zinc ion battery is significantly improved Stability and rate performance.
Patent Information
- Application Number
- CN202411319677.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-20
- Publication Date
- 2024-12-20
AI Technical Summary
The positive electrode material of zinc ion battery has poor structural stability and low conductivity, the voltage window of the aqueous electrolyte is narrow, the temperature adaptability is poor and easy to decompose. The high redox potential of zinc negative electrode and the dendrites and side reaction problems during the cycle seriously affect the battery. Energy density and cycle life.
A carbon cloth is used as a carrier to load VO2 nanosheets. By introducing oxygen vacancies between VO2 and the carbon cloth, V-C bond is constructed, and the interface stability between VO2 and the carbon cloth is improved, and a self-supported VO2 nanosheet electrode is prepared.
It significantly improves the structural stability and electrochemical performance of VO2/carbon cloth composite material, enhances the cyclic stability and rate performance of the positive electrode material of zinc ion battery, and the first reversible specific capacity reaches 636mAh g-1 at 0.1C current density, 10C The reversible specific capacity under current density is 242.2mAh g-1, and the capacity retention rate after 800 cycles at 10C current density is 99.6%.
Smart Images

Figure CN119170732A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of zinc ion battery electrode materials, and in particular to a preparation method and application of a self-supporting VO2 nanosheet electrode. Background Art
[0002] As an efficient and environmentally friendly electrochemical energy storage technology, lithium batteries have high energy density, long cycle life and no memory effect. They have been widely used in electric vehicles, smart phones, aerospace, medical devices and other fields.
[0003] Lithium ore resources are scarce (0.0017wt% in the earth's crust) and unevenly distributed. The high price of raw materials and the cost of mining and transportation limit the further large-scale development of lithium-ion batteries and electrochemical energy storage technology. In addition, lithium-ion batteries use flammable liquid organic electrolytes, which leads to serious safety issues during use.
[0004] In recent years, aqueous zinc-ion batteries have become one of the most promising new energy storage technologies due to their superior electrochemical performance and extremely high safety. Compared with other metal elements, zinc has significant advantages in resource reserves, theoretical capacity, chemical stability, electrochemical stability, and safety, allowing metallic zinc to be directly used as the negative electrode of the battery and operate stably in medium and weak acidic aqueous solutions. In addition, compared with the organic electrolytes widely used in lithium-ion batteries, aqueous zinc-ion electrolytes not only have ultra-high conductivity, but also have safety advantages such as non-toxicity and non-flammability. The above characteristics make aqueous zinc-ion batteries very promising for use in the future large-scale energy storage field.
[0005] However, the zinc-ion battery system still has many development bottlenecks: (1) the poor structural stability and low conductivity of the positive electrode material; (2) the narrow voltage window of the aqueous electrolyte, poor temperature adaptability and easy decomposition; (3) the high redox potential of the zinc negative electrode and the problems of dendrites and side reactions during the cycle. These problems interact with each other and work together, seriously affecting the selection of positive electrode materials and the energy density and cycle life of the battery.
[0006] The positive electrode material is an important component of zinc-ion batteries. Common aqueous zinc-ion battery positive electrode materials can be mainly divided into the following categories: vanadium-based materials, manganese-based materials, Prussian blue analogs, organic materials and other transition metal compounds and frameworks with redox activity, layered materials, etc.
[0007] Vanadium-based materials are excellent cathode materials for aqueous zinc-ion batteries. Multivalent vanadium can achieve multi-step redox, giving vanadium-based materials a high theoretical specific capacity. Moreover, vanadium-based materials show suitable
[0008] The voltage platform is about 0.8-1.0 V (vs. Zn / Zn2+ ). At the same time, the easily deformable VO polyhedron phase
[0009] The interconnected structure gives vanadium-based materials extremely strong designability.
[0010] Among the many vanadium oxides, VO2 with an oxidation state of +4 has also received widespread attention. VO2 is composed of VO6 octahedrons in a shared edge manner. Unlike V2O5, where the layers are connected by van der Waals forces, the layers of VO2 are connected in a shared angle manner. Such a structure exhibits better lattice shear resistance during electrochemical cycling and has very good structural stability.
[0011] However, the large band gap of VO2 leads to slow electron transfer rate and reduced battery rate performance. The main method at present is to use carbon coating technology to construct VO2 / carbon composite materials to improve the overall conductivity of the electrode and enhance its electrochemical performance as a positive electrode material for zinc ion batteries.
[0012] Although carbon coating can improve the electronic conductivity of VO2, the interface contact between VO2 and carbon cloth is poor. During the long cycle of the electrode, VO2 is easy to fall off from the surface of the carbon cloth, resulting in the collapse of the electrode structure and the attenuation of the electrochemical performance of the battery. In addition, the traditional electrode preparation process includes pulping-coating-drying-cutting and other processes, in which the inactive substances such as conductive agents, binders and solvents involved will affect the electrochemical performance of zinc-ion batteries.
[0013] Therefore, how to construct self-supporting VO2 / carbon composites and improve the interfacial contact between VO2 and carbon layer is the key to improving the electrochemical performance of VO2 / carbon composites. Summary of the invention
[0014] The purpose of the present invention is to provide a preparation method and application of a self-supporting VO2 nanosheet electrode, using carbon cloth as a carrier to load VO2 nanosheets to construct an integrated self-supporting electrode. Oxygen vacancies are introduced between VO2 and carbon cloth, and VC bonds are constructed at the interface between the two phases to improve the interface stability between VO2 and carbon cloth, so as to overcome the shortcomings of the prior art.
[0015] To achieve the above object, the present invention provides the following technical solution: A method for preparing a self-supporting V02 nanosheet electrode, comprising: step 1, dissolving 10 mmol of ammonium metavanadate and 20 mmol of oxalic acid in 40 mL of deionized water, stirring until completely dissolved, then adding 0.8 mmol of hexamethylenetetramine, and continuing stirring for 4 hours to obtain a blue solution S1;
[0016] Step 2: Place the mixed solution in a 50 ml reactor, and place a 2*4 cm piece of carbon cloth to ensure that the carbon cloth is completely immersed in the solution; place the reactor in an oven at 120-150°C for 2-4 hours, and cool it naturally to room temperature after the reaction is completed. Wash the obtained product with deionized water, and dry it in a vacuum drying oven at 60°C for 12-24 hours to obtain NH4V4O 10 / Carbon cloth integrated precursor S2;
[0017] The integrated precursor S2 is placed in a tube furnace and kept at 400-500°C for 4-6 hours in an Ar gas atmosphere to obtain a self-supporting VO2 nanosheet.
[0018] The amounts of ammonium metavanadate, oxalic acid and hexamethylenetetramine used in step 1 are 10 mmol, 20 mmol and 0.8 mmol respectively.
[0019] The amount of deionized water used in step 1 is 40 mL.
[0020] The specification of the reaction kettle in step 2 is 50mL.
[0021] The size of the carbon cloth in step 2 is 2*4cm.
[0022] The holding temperature of the oven in step 2 is 160°C.
[0023] The holding time of the oven in step 2 is 2 hours, 3 hours and 4 hours respectively.
[0024] The heat treatment temperature in step 3 is 450°C.
[0025] The heat treatment time in step 3 is 3 hours.
[0026] A self-supporting VO2 nanosheet electrode is used in a zinc ion battery. The self-supporting VO2 nanosheet electrode is obtained by the above-mentioned preparation method.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] The present invention utilizes oxygen vacancies to enhance the interface contact between VO2 and carbon cloth, thereby improving the structural stability of the VO2 / carbon cloth composite electrode and enhancing the electrochemical performance of the VO2 / carbon cloth electrode as a positive electrode material for zinc ion batteries. The introduction of oxygen vacancies can induce the formation of VC bonds between VO2 and carbon cloth, enhance the interface contact between VO2 and carbon cloth, and increase the binding energy between VO2 and carbon cloth from 2.3eV to 3.9eV. The structural stability of the VO2 / carbon cloth composite material exhibits excellent cycle stability and rate performance when used as a positive electrode material for zinc ion batteries. The first reversible specific capacity at a current density of 0.1C is 636mAh g -1The reversible specific capacity is 242.2 mAh g at a current density of 10C. -1 The capacity retention rate is 99.6% after 800 cycles at 10C current density. The self-supporting VO2 / carbon cloth composite material assembled zinc ion battery has excellent rate performance and cycle stability during testing.
[0029] In the present invention, carbon cloth is used as a current collector to prepare an integrated electrode, avoiding the slurry, pole piece production and rolling processes in the traditional electrode production process. At the same time, the zinc ion battery electrolyte is acidic, and the use of carbon cloth can prevent the dissolution of traditional current collectors (copper and aluminum) in aqueous electrolytes.
[0030] The preparation method provided by the invention is simple and reasonable, and has low cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 This is a physical picture of the self-supporting VO2 nanosheet electrode obtained according to the method of the present invention;
[0032] Figure 2 is a SEM image of a self-supporting VO2 nanosheet electrode obtained according to the method of the present invention;
[0033] Figure 3 1 is a cycle performance diagram of the positive electrode materials of Example 1 and Comparative Example 1 and Comparative Example 2 of the present invention at a current density of 0.1C;
[0034] Figure 4 It is a rate performance diagram of the positive electrode materials of Example 1 and Comparative Example 1 and Comparative Example 2 of the present invention;
[0035] Figure 5 It is a cycle performance diagram of the positive electrode materials of Example 1 of the present invention and Comparative Example 1 and Comparative Example 2 at a current density of 10C. DETAILED DESCRIPTION
[0036] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0037] Example 1
[0038] The preparation of a self-supporting VO2 nanosheet with high oxygen vacancy concentration and the comparison of its electrochemical performance as a positive electrode material for zinc ion batteries are as follows:
[0039] 10mmol ammonium metavanadate and 20mmol oxalic acid were dissolved in 40mL deionized water and stirred until completely dissolved. Then 0.8mmol hexamethylenetetramine was added and stirred for 4 hours until the solution turned blue. The mixed solution was poured into the lining of a 50ml reactor and carbon cloth was placed in it to ensure that the carbon cloth was completely soaked in the solution. The reactor was placed in a 150℃ oven for 3 hours. After the reaction was completed, it was naturally cooled to room temperature. The obtained product was washed with deionized water and dried in a vacuum oven at 60℃ for 12 hours to obtain NH4V4O 10 / carbon cloth integrated precursor, named NH4V4O 10 / Carbon cloth-1. NH4V4O 10 / Carbon cloth-1 was placed in a tube furnace under nitrogen atmosphere at 2℃min -1 The temperature was raised to 400°C, then kept at this temperature for 4 hours and then cooled to room temperature to obtain VO2 / carbon cloth-1.
[0040] Comparative Example 1
[0041] The preparation of a self-supporting VO2 nanosheet with low oxygen vacancy concentration and the comparison of its electrochemical performance as a positive electrode material for zinc ion batteries are described in the following specific steps:
[0042] 10mmol ammonium metavanadate and 20mmol oxalic acid were dissolved in 40mL deionized water and stirred until completely dissolved. Then 0.8mmol hexamethylenetetramine was added and stirred for 4 hours until the solution turned blue. The mixed solution was poured into the lining of a 50ml reactor and carbon cloth was placed in it to ensure that the carbon cloth was completely soaked in the solution. The reactor was placed in a 150℃ oven for 2 hours. After the reaction was completed, it was naturally cooled to room temperature. The obtained product was washed with deionized water and dried in a vacuum oven at 60℃ for 12 hours to obtain NH4V4O 10 / carbon cloth integrated precursor, named NH4V4O 10 / Carbon cloth-2. NH4V4O 10 / Carbon cloth-2 was placed in a tube furnace under nitrogen atmosphere at 2℃min -1 The temperature was raised to 400°C, then kept at this temperature for 4 hours and then cooled to room temperature to obtain VO2 / carbon cloth-2.
[0043] Subsequently, the hydrothermal reaction holding time was changed to 3 hours, and the obtained product was named NH4V4O 10 / Carbon cloth-2.
[0044] Comparative Example 2
[0045] Preparation of a VO2 / carbon composite nanosheet and comparison of its electrochemical performance as a positive electrode material for zinc ion batteries. The specific implementation steps are as follows: 10mmol ammonium metavanadate and 20mmol oxalic acid are dissolved in 40mL deionized water, stirred until completely dissolved, then 0.8mmol hexamethylenetetramine and 0.1mmol glucose are added, and stirring is continued for 4 hours until the solution turns blue. The above mixed solution is poured into the lining of a 50ml reactor, and carbon cloth is placed to ensure that the carbon cloth is completely immersed in the solution. The reactor is placed in a 150℃ oven for 4 hours, and after the reaction is completed, it is naturally cooled to room temperature. The obtained product is washed with deionized water and dried in a vacuum drying oven at 60℃ for 12 hours to obtain NH4V4O 10 / glucose precursor, named NH4V4O 10 / C. NH4V4O 10 / C was placed in a tube furnace under Ar atmosphere at 2℃min -1 The temperature was raised to 400°C, then kept at this temperature for 4 hours and then cooled to room temperature to obtain VO2 / C composite materials.
[0046] Due to the different hydrothermal reaction times, the oxygen vacancy concentration in Example 1 can reach 9.6%, while the oxygen vacancy concentration in Comparative Example 1 is only 2.1%.
[0047] like Figure 3 , 4 As shown in Figure 5, the VO2 / C composite material prepared by the method of Example 1 was assembled into a zinc ion battery, and the first reversible specific capacity at a current density of 0.1C was 636 mAh g -1 The reversible specific capacity is 242.2 mAh g at a current density of 10C. -1 , the capacity retention rate is 99.6% after 800 cycles at 10C current density.
[0048] By comparing the electrochemical properties of the VO2 / carbon cloth positive electrode materials of Example 1 and Comparative Examples 1 and 2, it can be found that the increase in oxygen vacancy concentration can enhance the cycle stability, rate performance and high current stability of the self-supporting VO2 nanosheet electrode when used as a positive electrode material for zinc ion batteries.
[0049] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a self-supporting VO2 nanosheet electrode, characterized in that The following steps are involved: Step 1): dissolving ammonium metavanadate and oxalic acid in deionized water, stirring until completely dissolved, then adding hexamethylenetetramine, and continuing to stir to obtain a blue solution S1; Step 2): Add solution S1 into the reactor, and then completely immerse the carbon cloth in the solution; The reactor was then placed in an oven for heat preservation, and after the reaction was completed, it was naturally cooled to room temperature, and the obtained product was washed and dried to obtain NH4V4O 10 / Carbon cloth integrated precursor S2; Step 3): Place the integrated precursor S2 in a tubular furnace and introduce nitrogen for heat treatment to obtain a self-supporting VO2 nanosheet electrode.
2. The method for preparing a self-supporting VO2 nanosheet electrode according to claim 1, characterized in that: The amounts of ammonium metavanadate, oxalic acid and hexamethylenetetramine used in step 1 are 10 mmol, 20 mmol and 0.8 mmol respectively.
3. The method for preparing a self-supporting VO2 nanosheet electrode according to claim 1, characterized in that: The amount of deionized water used in step 1 is 40 mL.
4. The method for preparing a self-supporting VO2 nanosheet electrode according to claim 3, characterized in that: The specification of the reaction kettle in step 2 is 50mL.
5. The method for preparing a self-supporting VO2 nanosheet electrode according to claim 1, characterized in that: The size of the carbon cloth in step 2 is 2*4cm.
6. The method for preparing a self-supporting VO2 nanosheet electrode according to claim 1, characterized in that: The holding temperature of the oven in step 2 is 160°C.
7. The method for preparing a self-supporting VO2 nanosheet electrode according to claim 1, characterized in that: The heat preservation time of the oven in step 2 is 2 hours, 3 hours and 4 hours respectively.
8. The method for preparing a self-supporting VO2 nanosheet electrode according to claim 1, characterized in that: The heat treatment temperature in step 3 is 450°C.
9. The method for preparing a self-supporting VO2 nanosheet electrode according to claim 1, characterized in that: The heat treatment time in step 3 is 3 hours.
10. Application of a self-supporting VO2 nanosheet electrode in a zinc ion battery, characterized in that: The self-supporting VO2 nanosheet electrode is obtained by any preparation method according to claims 1 to 9.
